Impact of Global Warming in Subtropical Climate Buildings: Future Trends and Mitigation Strategies - Marta Videras Rodríguez; Antonio Sánchez Cordero; Sergio Gómez Melgar; José Manuel Andújar Márquez (Energies, 2020)
The growing concern about global climate change extends to different professional sectors. In the building industry, the energy consumption of buildings becomes a factor susceptible to change due to the direct relationship between the outside temperature and the energy needed to cool and heat the internal space. This document aims to estimate the energy consumption of a Minimum Energy Building (MEB) in different scenarios—past, present, and future—in the subtropical climate typical of seaside cities in Southern Spain. The building energy consumption has been predicted using dynamic building energy simulation software tools. Projected climate data were obtained in four time periods (Historical, the 2020s, 2050s, and 2080s), based on four emission scenarios defined by the Intergovernmental Panel on Climate Change (IPCC): B1, B2, A2, A1F1. This methodology has been mathematically complemented to obtain data in closer time frames (2025 and 2030). In addition, different mitigation strategies have been proposed to counteract the impact of climate change in the distant future. The different energy simulations carried on show clearly future trends of growth in total building energy consumption and how current building designers could be underestimating the problem of air conditioning needs in the subtropical zone. Electricity demand for heating is expected to decrease almost completely, while electricity demand for cooling increases considerably. The changes predicted are significant in all scenarios and periods, concluding an increase of between 28–51% in total primary energy consumption during the building life cycle. The proposed mitigation strategies show improvements in energy demands in a range of 11–14% and they could be considered in the initial stages of project design or incorporated in the future as the impact of climate change becomes more pronounced.